2013
DOI: 10.1007/s00246-013-0737-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Aortic Aneurysm After Treatment of Coarctation

Abstract: Isolated coarctation of the aorta (CoA) occurs in 6-8 % of patients with congenital heart disease. After successful relief of obstruction, patients remain at risk for aortic aneurysm formation at the site of the repair. We sought to determine the diagnostic utility of echocardiography compared with advanced arch imaging (AAI) in diagnosing aortic aneurysms in pediatric patients after CoA repair. The Congenital Heart Databases from 1996 and 2009 were reviewed. All patients treated for CoA who had AAI defined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This finding is potentially important because this hemodynamic alteration could result in subsequent aortopathy at sights of elevated WSS. 37,38 While we noted reduced mean WSS sys in patients with unrepaired coarctation, the conclusions we can draw are limited by the small number of patients (n = 3) that made up this group. Moreover, this cohort tended to be younger and have reduced BSA.…”
Section: Discussionmentioning
confidence: 54%
“…This finding is potentially important because this hemodynamic alteration could result in subsequent aortopathy at sights of elevated WSS. 37,38 While we noted reduced mean WSS sys in patients with unrepaired coarctation, the conclusions we can draw are limited by the small number of patients (n = 3) that made up this group. Moreover, this cohort tended to be younger and have reduced BSA.…”
Section: Discussionmentioning
confidence: 54%
“…In the CCISC report, it was noted that the incidence of AWI decreased over the study period, 10 and in the study by Hoffman et al, 22 the authors reported a higher incidence of follow-up aneurysms in patients who were initially treated beyond 1 year of age and those who had ≥3 CoA procedures. There is a suggestion in the literature that late aneurysm formation may be more common after treatment of native than recurrent CoA.…”
Section: Natural History Of Early Awi and Development Of New Aortic Wmentioning
confidence: 93%
“…22 Isolated bicuspid AOV, occurring in 1% to 2% of the population, is identified in 9% to 24% of cases of aortic dissection, with most showing some degree of CMN in addition to underlying hypertension. The association between CoA, bicuspid AOV, and CMN suggests an interaction among these factors or a unifying arteriopathy, which could predispose to AWI.…”
Section: Bicuspid Aovmentioning
confidence: 99%
See 2 more Smart Citations